Economies of scale and scope in the Finnish non-life insurance industry - Toivanen, Otto (Journal of Banking & Finance, 1997)
Economies of scale and scope in Finnish non-life insurance are studied. The production process is separated into cost and portfolio management functions. Firms expand their branch network to either gain market power or informational advantages. There are diseconomies of scale at firm and economies of scale at branch level, and economies of scope in production. Large firms in the non-life insurance industry pay a substantial premium to gain market power via branch networks. The retained premiums-curve of portfolio management is U-shaped and a positive function of the number of branches.